Prevention Strategies to Address Problematic Gaming: An Evaluation of Strategy Support Among Habitual and Problem Gamers - Stevens, Matthew W. R. (J Prim Prev, 2021)
Psychosocial problems arising from excessive gaming are a public health issue across the developed world. In its most serious form, problematic gaming is recognized as gaming disorder (GD) in the ICD-11. Research has tended to focus on the value of outpatient treatment for GD, but less attention has been paid to broader prevention strategies to address less serious but nevertheless harmful gaming behaviors. Another gap in this literature has been the lack of involvement of the gaming community as stakeholders to identify feasible prevention approaches. This study investigated: (1) regular and problematic gamers’ level of support for different prevention strategies within primary, secondary, and tertiary approaches; and, (2) whether self-efficacy is associated with greater support for prevention strategies, as predicted by the Health Belief Model. A total of 992 participants completed an online survey that evaluated support for problem gaming prevention strategies and included measures of self-efficacy, gaming involvement, and GD symptoms, psychological distress, and mental health help-seeking behaviors. Participants reported stronger support for primary prevention strategies, including education, screening, and warning labels, than for other prevention approaches. Overall, 61% of participants expressed support for primary prevention as compared to secondary (39%) and tertiary (36%) approaches. There was stronger support for outpatient care (48%) than inpatient services (25%). In-game shutdown features received the lowest support (65% disapproval). Contrary to the Health Belief Model, self-efficacy was not associated with prevention support. Younger, female, and less frequent gamers were more likely to support primary and secondary prevention strategies. These findings suggest that gamers may be more favorable toward prevention measures aligned with informed decision-making, autonomy, and self-directed actions. Gamers may be strongly opposed to modifications to the structure of gaming activities (e.g., shutdown features). Future research should evaluate the efficacy and cost-effectiveness of problem gaming prevention measures in different populations and regions.